Effect of Cold Plasma Treatment and Priming in Bell Pepper (Capsicum annuum L.) - Nalwa, Cherry; Thakur, Ashok K.; Vikram, Amit; Rane, R.; Vaid, A. (International Journal of Bio-resource and Stress Management, 2017)
The present investigation was conducted at Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan (HP) during kharif 2014 to study the “Effect of cold plasma treatment and priming on bell pepper (Capsicum annuum L. cultivar California Wonder). The experiment was laid out in Randomized Block Design (Factorial) in the field. The seeds were exposed to various durations of oxygen cold plasma treatment using glow discharge technique at FCIPT, Institute for Plasma Research, Gandhinagar, Gujarat, India. Seeds were pre-treated with power of 100 W oxygen gas was used at base pressure of 0.05m bar, operating pressure of 0.2 m bar, voltage of 500 V and current of 0.2A for treatment durations of 0, 3, 6, 9, 12, 15 minutes, The changes in surface morphology of plasma treated seeds were studied by Scanning Electron Microscopy (SEM) and Contact Angle Goniometer. Treatments comprised of primed and non-primed seeds and seven seed plasma treatments. Along with plasma treatment, seeds were also treated with standard osmopriming method for comparison. The plasma treatment alone as well as in combination with osmopriming up to 6 minutes plasma treatment was found superior over all treatments in terms of growth characters, fruit yield characters and seed yield characters. Osmoprimed seeds exposed with 6 minutes plasma were also found to be best treatment for most of the traits recording days to 50% flowering (45.33 days), fruit yield plant-1 (1.00 kg), ripe fruit yield plant-1 (830.35 g) and seed yield per plant (10.74 g).